2007
DOI: 10.1523/jneurosci.1571-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

NAC1 Regulates the Recruitment of the Proteasome Complex into Dendritic Spines

Abstract: Coordinated proteolysis of synaptic proteins is required for synaptic plasticity, but a mechanism for recruiting the ubiquitin-proteasome system (UPS) into dendritic spines is not known. NAC1 is a cocaine-regulated transcriptional protein that was found to complex with proteins in the UPS, including cullins and Mov34. NAC1 and the proteasome were cotranslocated from the nucleus into dendritic spines in cortical neurons in response to proteasome inhibition or disinhibiting synaptic activity with bicuculline. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 53 publications
5
55
0
Order By: Relevance
“…Shen et al have recently demonstrated that proteasome inhibition or bicuculline disinhibition in cultured hippocampal neurons caused translocation of the proteasome from nucleus to cytoplasm [114]. We have discovered a similar shift of UPS components from nucleus to cytoplasm upon transgenic proteasome inhibition in Drosophila, where ubiquitinated proteins no longer accumulated in the nucleus after acute proteasome inhibition (Fig.…”
Section: Ups Trafficking In Synapse Regulationsupporting
confidence: 59%
See 1 more Smart Citation
“…Shen et al have recently demonstrated that proteasome inhibition or bicuculline disinhibition in cultured hippocampal neurons caused translocation of the proteasome from nucleus to cytoplasm [114]. We have discovered a similar shift of UPS components from nucleus to cytoplasm upon transgenic proteasome inhibition in Drosophila, where ubiquitinated proteins no longer accumulated in the nucleus after acute proteasome inhibition (Fig.…”
Section: Ups Trafficking In Synapse Regulationsupporting
confidence: 59%
“…Shen et al show that a 19S ATPase regulatory proteasome subunit, Mov34, complexes with a subunit of the SCF E3 ligase complex, Cul3, and an immediate early gene, NAC1, that is upregulated after psychostimulant-induced behavioral plasticity. Heightened synaptic activity promotes rapid and persistent NAC1-dependent translocation of the proteasome and Cul3 to the region of postsynaptic dendritic spines [114]. The activity-dependent trafficking of proteasomes and associated UPS machinery provides an exciting mechanism for tuning local protein degradation by coupling synaptic activity levels with proteasome availability.…”
Section: Ups Trafficking In Synapse Regulationmentioning
confidence: 99%
“…This redistribution was found to be dependent upon NMDA receptor activation (63). A subsequent report showed that NAC1, a cocaine-regulated transcriptional protein that interacts with the proteasome, regulates the trafficking of the proteasome in an activity-dependent manner (64). These data suggest that synaptic activity can promote the recruitment and sequestration of proteasomes to locally remodel the protein composition of synapses.…”
Section: Discussionmentioning
confidence: 87%
“…Because CaMKII-dependent phosphorylation of Rpt6 did not directly regulate proteasome activity in vitro, we hypothesize that other regulatory factors, not present in our reconstituted and highly purified in vitro assay, may be required. Associated proteins have previously been found to regulate various aspects of proteasome function (23,64,74). Interestingly, both proteasome and CaMKII translocate from dendritic shaft to dendritic spine compartments in response to neuronal activity in a similar timeframe (63,75,76).…”
Section: Discussionmentioning
confidence: 95%
“…It will also be important to uncover molecular mechanisms linking cocaine to UPS regulation (eg, Shen et al, 2007). However, our study-the first to examine the role of the UPS in retrieval of cocaine memories following cocaine selfadministration, as well as the first to examine the UPS following retrieval in any operant learning paradigm or after a delay between training and testing-provides an important framework for future studies by revealing that the involvement of the UPS in memory retrieval depends greatly upon paradigm, brain region, and the age of the memory.…”
Section: Discussionmentioning
confidence: 99%